Transumbilical laparoendoscopic single-site adrenalectomy: A feasible and safe alternative to standard laparoscopy - João André Carvalho; Pedro Tiago Nunes; Hugo Antunes; Belmiro Parada; Edson Retroz; Edgar Tavares-da-Silva; Isabel Paiva; Arnaldo José Figueiredo (Archivio Italiano di Urologia e Andrologia, 2019)
Objectives: Standard multi-port laparoscopic adrenalectomy (LA) is considered the gold standard for benign adrenal tumors. Single-site LA has been proposed as a feasible and safe alternative because of lower invasiveness, improved cosmetics, less pain and shorter hospital stay. The objective was to evaluate and compare results of single-site transumbilical laparoendoscopic adrenalectomy with standard LA for adrenal tumors. Materials and methods: One hundred consecutive adrenalectomies from 93 patients, performed between March 2009 and June 2017, were laparoscopically excised: 59 by standard multi-port LA (group 1) and 41 by transumbilical laparoendoscopic single-site adrenalectomy (group 2). Data gathered included demographics, comorbidities, preoperative imaging, tumor characteristics, perioperative data, surgical complications, pathology and follow-up. IBM SPSS Statistics 23 software was used and p value < 0.05 was considered significant. Results: Patients of group 2 were younger (48.7 ± 13.9 versus 59.7 ± 15.1 years; p < 0.001) and had fewer comorbidities (p < 0.05). Mean tumor diameter in group 2 was lower than those of group 1 (27.52 ± 14.3 versus 47.9 ± 30.6 mm; p < 0.001). Tumor laterality did not influence the choice of technique nor the surgical morbidity. All procedures were successfully completed, although one standard LA needed conversion to open surgery. Mean operative time, hemorrhagic losses, postoperative opioid analgesic requirement and hospital stay were not statistically different between groups. Most patients in group 2 (31 patients, 85.4%) did not require drainage, compared to 14 (25.4%) patients of group 1 (p < 0.001). Patients who underwent single-site LA resumed normal diet earlier (1.0 ± 0.2 versus 1.6 ± 0.7 days; p < 0.001). There were no reoperations and no perioperative mortality. Overall mean follow-up time was 94.9 ± 3.1 months, not statiscally different between groups (p = 0.7). Conclusions: Our results revealed that transumbilical approach for laparoendoscopic single-site adrenalectomy for adrenal tumors is a feasible and safe alternative to standard laparoscopic adrenalectomy.